Pembelajaran Inklusi Pajak Berbasis PBL: Proyek Pengembangan E-Filing Pajak Penghasilan Versi Edukasi - Jasmine Afifah; Arniati Arniati; Mega Mayasari; Viona Salsabila Anggreini; Siska Ayu Yulianingsih (Pusat P2M Politeknik Negeri Batam, 2023)
This research aims to determine whether a tax inclusion program through Project Based Learning (PBL) in developing an educational version of e-filing tax application can educate students about taxation and how to report taxes. The research also aims to understand the implications of tax inclusion through PBL in developing the educational version of e-filing tax application on students' tax awareness. The sampling was done using purposive sampling technique, with the criteria of fourth, sixth, and eighth semester students from the Department of Computer Engineering and the Department of Business Management at Batam State Polytechnic who were directly involved in the process of developing the educational version of e-filing tax application project. This research is a qualitative descriptive study. The results of this research show that the implementation of tax inclusion through PBL has successfully educated students about taxation. This includes understanding of PPh, NPWP, EFIN and the differences in SPT, which include SPT 1770SS, 1770S, and 1770 for individual taxpayers, and SPT 1771 for corporate taxpayers. The implications of the tax inclusion program through PBL have led to an increase in students' tax awareness, as evidenced by their understanding of tax benefits and their awareness and willingness to report and pay taxes.